2001
DOI: 10.1021/es0017615
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Very Hydrophobic Organic Compounds (VHOCs) on Dissolved Humic Organic Matter (DOM). 2. Measurement of Sorption and Application of a Flory−Huggins Concept To Interpret the Data

Abstract: Sorption phenomena of very hydrophobic compounds (VHOCs, log K(OW) > 5) on dissolved humic organic matter (DOM) are overwhelmingly based on partitioning processes. In this respect, DOM is very similar to "rubbery" soil/sediment OM. To exclude system adsorption effects, the DOM sorption coefficients (K(DOM)) of VHOCs were determined using a dynamic approach based on the VHOCs' aqueous solubility enhancement in the presence of DOM. Partition coefficients are strongly correlated to the analytes' Kow across the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 39 publications
7
60
0
Order By: Relevance
“…As a first approximation, we adopted in this study the one proposed by Poerschmann and Kopinke. 36 DOC concentration data for the ECS were taken from Hung et al 37 3. RESULTS AND DISCUSSION 3.1.…”
Section: Methodsmentioning
confidence: 99%
“…As a first approximation, we adopted in this study the one proposed by Poerschmann and Kopinke. 36 DOC concentration data for the ECS were taken from Hung et al 37 3. RESULTS AND DISCUSSION 3.1.…”
Section: Methodsmentioning
confidence: 99%
“…Biomimetic SPME has been widely applied to study the bioconcentration toxicity effect and uptake kinetics of OCs in aquatic biota [5,20,29,30,38,39,61]. Leslie et al [61] used an 85 μm polyacrylate (PA) coating to mimic the uptake of 2,4,5-trichloroaniline and 1,2,3,4-tetrachlorobenzene by midge larvae.…”
Section: Determination Of Sorption Coefficient Using Nd-spmementioning
confidence: 99%
“…Several studies have showed that the DOM increases the solubility [4], decreases the volatilization [5], and also affects the bioavailability and toxicity of the OCs [6,7], as well as controls the leaching of pesticides in soil [8][9][10][11]. In addition, the presence of DOM enhances the photodegradation of pollutants through the production of reactive species such as hydroxyl radical or singlet oxygen [12], and inhibits the degradation of pesticides [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…1. This method is suitable for the measurement of the freely available PAH and consequently also for the bioavailable PAH fraction in water samples (Poerschmann and Kopinke 2001;Ramos et al 1998). HS-SPME kinetics were modeled and fitted to experimental data obtained by performing extractions at different exposure times.…”
Section: Spme Kinetic Parameters and Free Pah Determinationmentioning
confidence: 99%
“…These binding interactions can be partitioning or adsorption phenomena, depending on the nature of the organic matter (Poerschmann and Kopinke 2001). The distribution or partitioning of non-ionic hydrophobic organic compounds like PAH between water and soil or sediment has been shown to depend primarily on the hydrophobicity of the compounds and on the fraction of organic carbon in the sorbent (Schlautman and Morgan 1993).…”
mentioning
confidence: 99%